6x+6=-71+5x

Simple and best practice solution for 6x+6=-71+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+6=-71+5x equation:


Simplifying
6x + 6 = -71 + 5x

Reorder the terms:
6 + 6x = -71 + 5x

Solving
6 + 6x = -71 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
6 + 6x + -5x = -71 + 5x + -5x

Combine like terms: 6x + -5x = 1x
6 + 1x = -71 + 5x + -5x

Combine like terms: 5x + -5x = 0
6 + 1x = -71 + 0
6 + 1x = -71

Add '-6' to each side of the equation.
6 + -6 + 1x = -71 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = -71 + -6
1x = -71 + -6

Combine like terms: -71 + -6 = -77
1x = -77

Divide each side by '1'.
x = -77

Simplifying
x = -77

See similar equations:

| n=4/0.5 | | n=4/0.25 | | n=4*0.5 | | 46-n=23 | | 11n=165 | | 2xsquared=7-x | | 4x+12Y=20 | | 2ln(x-5)=4 | | 9r^2+48r+64= | | 180/n=90 | | z^2+(1+2i)z+(1+7i)=0 | | 64/n=2 | | 1.5x=-63 | | 4r^2-121f^2= | | 64/2n=2 | | 5n-2n=45 | | -3.1x=-34.1 | | eonx=2.4 | | 49s^2-100= | | 36w^2+60wd+25d^2= | | 0,25x=16 | | 2.5x=-80 | | (x^-0.6)/(x^0.4) | | n/3=31 | | 16a^2-72a+81= | | 0/5=n | | -3.7x=-66.6 | | 2iz+3=4i+5z | | 8x-11x=60 | | n*n=36 | | 367+500= | | 3.5x=-12 |

Equations solver categories